Social contributions to meaning in life: the role of romantic relationship quality, parenting, and gender - Gold, Alaina I.; Ryjova, Yana; Aviv, Elizabeth C.; Corner, Geoffrey W.; Rasmussen, Hannah F.; Kim, Yehsong; Margolin, Gayla (Frontiers in Psychology, 2024)
The present study tests the association between romantic relationship quality and number of children on meaning in life (i.e., sense of purpose, coherence, and significance) and considers interactions between these constructs and gender. A survey was conducted approximately one year into the pandemic among 473 individuals in the United States. Models demonstrated that relationship quality and number of children are positively associated with meaning, though relationship quality was more strongly related to meaning for men than women. We showed that for women there was an equally positive link between relationship quality and meaning regardless of number of children. However, for men, the positive association between relationship quality and meaning was strongest for those with more than one child, decreased in magnitude for those with one child, and was no longer significant for men with more than one child. These findings provide empirical evidence that social relationships benefit meaning in life and underscore the complexity of these associations. Results have implications for theoretical perspectives on meaning in life, as well as for policies that encourage family wellbeing.